Effect of a dual orexin receptor antagonist on Alzheimer's disease: Sleep disorders and cognition - Zhou, Mengzhen; Tang, Shi (Frontiers in Medicine, 2023)
In this review, we discuss the recent findings on basic research and clinical interventions regarding the involvement of the orexin system in AD.